The impacts of social and family prejudice on the mental health of lesbians, gays, bisexuals and transsexuals (Research, Society and Development, 2020)
The present study aimed to investigate the impacts of social and family prejudice on the mental health of LGBT individuals in the context of contemporary times. Specifically the objectives were: to understand the aspects that are linked to the prejudice experienced daily by LGBTs, which in most cases also suffer from lack of family support. Moreover, they often live with various issues related to discrimination and non-acceptance of oneself, as in some cases the sexual orientation of the individual can generate many frustrations and embarrassments. Thus, the lack of understanding and affection ends up generating very strong negative consequences, which can be both psychic and physical. A bibliographic search was conducted from September to November 2019 in the electronic databases: PePsic, Scielo, thesis and dissertation repositories of Brazilian universities, event annals, booklets and books. It was found that much of contemporary society still has a great intolerance to LGBTs, which generates prejudice and consequently violence. LGBTs are gaining more respect towards society, but still face many conflicts over their rights and freedom of expression. They also always seek a space in the collectivity, that is, they are in a constant struggle for egalitarianization and less pre-judgments, so possibly there will be a thought not as fragmented as it is about the theme addressed in this article.